Spatial distribution of prenatal indicators in the State of Tocantins 2001 to 2015 - Patrick Nunes Brito; Tássylla Caroline Ferreira Pereira; Durval Nolasco Neves Neto; Cristina Zanettini Ribeiro
Abstract Objectives: temporal-spatial analysis of prenatal indicators in the municipalities of the state of Tocantins based on the use of five-year intervals from 2001 to 2015. Methods: the indicators subject to analysis were: average prenatal care (APCPW), proportion of prenatal care in the first trimester (PPCFT) and proportion of pregnant women with vaccine on time (PWVT). Data from the DATASUS platform were used for spatialization of indicators through Thematic Maps, using the QGIS software. Results: indicators of proportion of prenatal care in the first trimester and proportion of pregnant women with vaccine on time showed gradual improvement in their indicators after 15 years of analysis, with values above 75% and 90%, respectively, showing compatibility with the current national scenario. However, APCPW has revealed that no municipality had more than 3 prenatal care visits within 15 years. Conclusions: among the indicators analyzed, the average of prenatal care, although it showed improvement in the 15-year interval, is the one with the greatest deficiency in the state and should therefore have a greater focus on primary care. Thus, it emphasizes the need to encourage the development of organized health systems and the use of specific policy actions to improve not only this indicator, but also the others, to improve prenatal quality.